Peningkatan Layanan Kesehatan pada Masyarakat dengan Profesi Tenaga Profesional Massage Care Melalui Pengetahuan Muskuloskeletal - Dwi Martha Nur Aditya; Winnie Nirmala Santosa (STIKes Surya Global Yogyakarta, 2021)
ABSTRACT Background of Study : Massage care services are complementary health services that are used to improve the quality of health conditions. Application of massage care services produce positive contribution for reducing pain, depression, and increasing immune system. Massage care services in private business have been performed by non-level therapists, with a good technical understanding but do not yet have theoretical basis to support the level of professionalism. Knowledge’s provision of musculoskeletal’s functional anatomy expected to increase the therapist's professionalism, which has an impact on improving the quality of public health services.Methods : This study used an experimental design, cross-sectional approach, pre-test post-test control group design. The population and sample of this study are massage care’s therapists in Surabaya. Data were analyzed using Pearson correlation test and paired sample t-test to describe the relationship between gender (JK), education level (TP) and knowledge of musculoskeletal’s functional anatomy (AFM).Results : The results of the Pearson correlation test show a negative correlation between JK and TP on AFM (p0.05; CI 95%). Meanwhile, the results of the different paired sample t-test showed that there were differences between pre-test (PRE) and post-test (POS) of AFM after the intervention. (p0.05; CI 95%).Conclusion : Improving the complementary health services through massage care to the community, possible to do by providing material for strengthening the theoretical basis for selecting massage techniques through knowledge’s provision of musculoskeletal’s functional anatomy.Keywords: Public Health, Health service, Health care quality, Massage care, Functional anatomy